Status of artificial sweeteners, glucose oxidase and some quality parameters of honey samples from the Asir region, Saudi Arabia - Badria M. AL-Shehri; Reham M. Mashat; Rahaf M.H. Alshareef; Wed Mohammed Ali Alaerjani; Khalid Ali Khan; Hamed A. Ghramh; Essam H. Ibrahim; Majed A. Bajaber; Abdulaziz A. Zarbah; Mohammed Elimam Ahamed Mohammed (Journal of King Saud University: Science, 2022)
Background: Artificial sweeteners are low calorie polyhydric alcohols produced from carbohydrates or amino acids. Presence of artificial sweeteners in honey is not investigated before. Objective: this study measured the concentration of Xylitol and Sorbitol, the activity of glucose oxidase (GOX) and the concentration of glucose and acidity of honey samples from Asir region-Saudi Arabia. Furthermore, the values of pH and electric conductivity were determined.MethodsThe floral origin of the honey samples were confirmed through pollen analysis. The PH, electric conductivity (EC.), acidity, and glucose concentration were measured according to the methods of international honey commission. The glucose oxidase activity and the concentration of xylitol and sorbitol were determined according to the instructions of Megazyme International kits CAT.#: K-GLOX and CAT.#: K-SORB, respectively. The statistical package for social sciences (SPSS)-version 20 was applied to analyze the obtained results.Results.The floral origin analysis showed that the honey samples were Acacia (8) and Zizphus (4). The altitudes of the Acacia honey samples were 900 and 2000 m above sea level while the Zizphus honey samples were collected from 900 m above sea level. The studied quality parameters (Glucose, PH, Acidity, and EC.) were within the range of the CODEX standards and the Saudi Food and Drug Authority guide for honey. Irrespective of the altitude, the glucose oxidase activity in the Acacia honey samples was (4.7 ± 1.13) whereas its activity of the Zizphus honey was (5.0 ± 1.62). There was insignificant difference between the glucose activity of the Acacia and Zizphus honey samples (p-value = 0.7). The concentration of xylitol and sorbitol were not affected by the floral origin (p-value ≥ 0.17).Conclusions.The Acacia and Ziziphus honey are characterized by containing high amounts of sorbitol and trace xylitol content. The floral origin and year of harvest significantly affected pH, EC and Acidity of the honey samples.